Distant inferior myocardial infarction with pathological Q-wave: a clinical case - K. G. Pereverzeva; S. S. Yakushin; S. A. Biryukov; N. N. Peregudova; Yu. O. Cherkasova (Рациональная фармакотерапия в кардиологии, 2025)
A clinical case of Q-myocardial infarction (MI) of the lower wall of the left ventricle in a 71-year-old patient with a history of MI in the presence of chronic occlusions of the right and circumflex coronary arteries (CA), extended narrowing of the intermediate branch in the upper and middle segments from 50 % to 80 % and stenosis of the anterior interventricular artery in the upper the 99% segment is described. Upon admission to the hospital, the patient’s ECG revealed a completely right bundle branch block and ST-segment elevation of up to 0.5 mm in lead III against the background of sinus rhythm. The diagnosis of myocardial infarction was confirmed by a diagnostically significant high-sensitivity troponin I level. The refusal of attempts to stent chronic occlusions of the right and circumflex CA and stenting of the proximal anterior interventricular artery led to relief of pain, stabilization of the patient’s condition and subsequent discharge from the hospital. Echocardiography at discharge revealed akinesia and mild bulging of the upper half of the left ventricular (LV) inferior wall, severe hypokinesia of the upper and middle thirds of the LV posterior wall, and hypokinesia of the upper third of the LV inferoseptal wall. The LV ejection fraction (Simpson’s method) was 44-45 %. The clinical case presented in the article demonstrates the importance of the correct management tactics for patients with distant MI, when the correct choice of infarct- related CA and its stenting led to a favorable outcome in an elderly patient with severe multivessel CA lesion and developed recurrent Q-lower distant MI.